Archaeal Chromatin Proteins Cren7 and Sul7d Compact DNA by Bending and Bridging - Zhenfeng Zhang; Zhengyan Zhan; Bing Wang; Yuanyuan Chen; Xiuqiang Chen; Cuihong Wan; Yu Fu; Li Huang (mBio, 2020)
ABSTRACT Archaeal chromatin proteins Cren7 and Sul7d from Sulfolobus are DNA benders. To better understand their architectural roles in chromosomal DNA organization, we analyzed DNA compaction by Cren7 and Sis7d, a Sul7d family member, from Sulfolobus islandicus at the single-molecule (SM) level by total single-molecule internal reflection fluorescence microscopy (SM-TIRFM) and atomic force microscopy (AFM). We show that both Cren7 and Sis7d were able to compact singly tethered λ DNA into a highly condensed structure in a three-step process and that Cren7 was over an order of magnitude more efficient than Sis7d in DNA compaction. The two proteins were similar in DNA bending kinetics but different in DNA condensation patterns. At saturating concentrations, Sis7d formed randomly distributed clusters whereas Cren7 generated a single and highly condensed core on plasmid DNA. This observation is consistent with the greater ability of Cren7 than of Sis7d to bridge DNA. Our results offer significant insights into the mechanism and kinetics of chromosomal DNA organization in Crenarchaea. IMPORTANCE A long-standing question is how chromosomal DNA is packaged in Crenarchaeota, a major group of archaea, which synthesize large amounts of unique small DNA-binding proteins but in general contain no archaeal histones. In the present work, we tested our hypothesis that the two well-studied crenarchaeal chromatin proteins Cren7 and Sul7d compact DNA by both DNA bending and bridging. We show that the two proteins are capable of compacting DNA, albeit with different efficiencies and in different manners, at the single molecule level. We demonstrate for the first time that the two proteins, which have long been regarded as DNA binders and benders, are able to mediate DNA bridging, and this previously unknown property of the proteins allows DNA to be packaged into highly condensed structures. Therefore, our results provide significant insights into the mechanism and kinetics of chromosomal DNA organization in Crenarchaeota.